(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
: This article explores the transformative role of cross-border e-commerce in fostering inclusive economic growth in emerging markets. It examines how digital trade platforms enable small and medium-sized enterprises (SMEs), women entrepreneurs, and rural communities to access international markets, reduce entry barriers, and increase income opportunities